2014
DOI: 10.3126/ije.v3i4.11728
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Assessment of Aridity Over Pakistan Provinces (1960-2009)

Abstract: Due to rapid growth of population, massive deforestation and anthropogenic activities, noticeable change in climate conditions is being observed in Pakistan. Increased aridity due to climate change is a growing environmental problem of the agricultural country like Pakistan. It is essential to assess and monitor aridity to combat the probable land degradation and drought desertification. Identification of arid and semi arid regions on climatic basis is the first essential step in any project of land reclamatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 4 publications
0
52
0
Order By: Relevance
“…Five different aridity indices have been used by taking the data of 54 climate stations to classify the climate of Pakistan during 1960–2009. This mapping identified that semi‐arid to extreme arid areas covers 75–88%, while the humid zone constitutes ∼0.1–13% (Haider and Adnan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Five different aridity indices have been used by taking the data of 54 climate stations to classify the climate of Pakistan during 1960–2009. This mapping identified that semi‐arid to extreme arid areas covers 75–88%, while the humid zone constitutes ∼0.1–13% (Haider and Adnan, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are two major precipitation seasons in Pakistan: monsoon precipitation during July to September (see, for instance, Wang, ) and winter precipitation during December to March due to western disturbances (see, for instance, Dimri et al, ). Annual precipitation for Pakistan varies from 30 to 400 mm from south to north (Haider and Adnan, ). Pakistan receives 60–65% (25–30%) of annual precipitation during monsoon (winter) season (see, for instance, Asmat and Athar, ).…”
Section: Study Area and Its Climatementioning
confidence: 99%
“…For Pakistan, there is no such SD analysis for wet and dry spells. Earlier climate classifications in Pakistan are based on: characteristic variations in temperature and precipitation (Ahmad, ; Shamshad, ), using ratio of precipitation and evaporation (Bharucha and Shanbhag, ), factor and cluster analysis (Oliver et al, ; Hussain and Lee, ), AI (Zahid and Rasul, ; Haider and Adnan, ), Köppen classification (Sarfaraz et al, ) and principal component analysis (Sarfaraz, ). Oliver et al .…”
Section: Introductionmentioning
confidence: 99%
“…They also noted that in the study, it was difficult to establish causality of illness or disease with exposure to PCBs. In the next paper, Haider and Adnan (2014) that through rapid growth of population, massive deforestation and anthropogenic activities, noticeable change in climate conditions is being observed in Pakistan. They use a Geographic Information System (GIS) for the assessment of aridity in Pakistan from climatic data of fifty years ) collected from fifty-four stations.…”
Section: Chakir Et Al (2014) Reported Morphosedimentary Study Of Allmentioning
confidence: 99%